(untitled) (Indian Journal of Child Health, 2019)
Hydronephrosis is enlargement of renal collecting system including renal calyces with or without ureters. It is the most common prenatal anomaly and accounts for about 30–50% prenatal ultrasonography anomalies. Urinary tract dilation occurs in 1/100 pregnancies (1%) and causes significant uropathy in 1/500 (0.2%) cases. Antenatal hydronephrosis means dilation of the fetal renal collecting system that could be detected on prenatal ultrasonography and the prevalence is between 0.5% and 4%. Outcome depends on the underlying etiology. The index case was prenatally discovered at a gestational age of 6 months and postnatal assessment revealed a Grade V hydronephrosis with the absence of excretion or function on the right side.